2009
DOI: 10.1111/j.1742-7843.2009.00466.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Uric Acid on Gentamicin‐Induced Nephrotoxicity in Rats – Role of Matrix Metalloproteinases 2 and 9

Abstract: In this work, we aimed to study the effect of uric acid on gentamicin-induced nephrotoxicity. Male Sprague-Dawley rats were assigned to one of six groups (six rats each) which received intraperitoneal injections for 9 days: (S) saline; (UA) Uric acid alone; (G) Gentamicin alone; (G + UA) Gentamicin + uric acid; (G rec) Gentamicin recovery and (G + UA rec) Gentamicin + uric acid recovery. In (G rec) and (G + UA rec), rats recovered for 7 days after the last injection. Urine and blood samples were taken on day 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 43 publications
2
23
2
1
Order By: Relevance
“…Especially, the perifilamentary MMP-2 expression was significantly diminished by mesh coating with a concentration of 8 μg/mg gentamicin at each time point. The effect of gentamicin on MMP-2 expression was likewise investigated in previous studies, but in contrast to these results, our findings demonstrate a presumably dose-dependent downregulation of the MMP-2 for the first time [21,46]. Such a dose-dependent effect of gentamicin is supported by the finding that the administration of gentamicin in nephrotoxic doses induces MMP-2 expression [47].…”
Section: Discussioncontrasting
confidence: 83%
“…Especially, the perifilamentary MMP-2 expression was significantly diminished by mesh coating with a concentration of 8 μg/mg gentamicin at each time point. The effect of gentamicin on MMP-2 expression was likewise investigated in previous studies, but in contrast to these results, our findings demonstrate a presumably dose-dependent downregulation of the MMP-2 for the first time [21,46]. Such a dose-dependent effect of gentamicin is supported by the finding that the administration of gentamicin in nephrotoxic doses induces MMP-2 expression [47].…”
Section: Discussioncontrasting
confidence: 83%
“…TQ supplementation after GEN injection reversed the decreased blood Cr, urea and lipid peroxides [26]. In agreement with other literatures, this work showed that GEN increases MDA level as an end product of lipid peroxidation and decreases the levels and activities of GSH, SOD and GPx [27]. Decreased lipid peroxidation and increased SOD and GPx activities after administration of TQ suggest that TQ ameliorates its antioxidant properties by scavenging the free radicals [28].…”
Section: Discussionsupporting
confidence: 77%
“…Gentamicininduced-nephrotoxicity can cause renal injuries due to ROS generation [4,14,15]. Antioxidant compounds such as melatonin [27], vitamin E and probacol [28] etc.…”
Section: Discussionmentioning
confidence: 99%
“…Thus; they are more sensitive to reactive oxygen species (ROS) effects. Gentamicin-induced nephrotoxicity increases the level of serum creatinine and urea, tubular necrosis and glomerular congestion but decrease glomerular filtration rate [13][14][15]. In studies done on antioxidant compounds such as curcumin [16] olive leaf extract [5], green tea and coenzyme Q10 [6] and rosmarinic acid [17] such as antioxidant compounds played effective roles in reduction or decrease of renal injuries caused by using of gentamicin.…”
Section: Introductionmentioning
confidence: 99%